Balancing the equation: assessing the impact of management practices on staff and faculty wellbeing in Chinese higher education institutions - Hu, Tingting (Frontiers in Psychology, 2024)
Introduction The intersection of work-family dynamics and job contentment has become a pivotal area of investigation within the higher education landscape, drawing scholarly attention, especially in the Chinese context. This study delves into the intricate relationship between work-family culture and job satisfaction, with a particular spotlight on the mediating influence of perceptions of organizational fairness. The impetus behind this emphasis lies in the burgeoning acknowledgment of organizational justice as a pivotal force shaping employee attitudes and conduct within academic establishments. Method This research was conducted using two distinct groups. The first group consisted of 1,075 faculty members at Chinese universities, while the second group comprised 972 administrative and technical employees at these institutions. Results The mediational analyses provided in this study offer an enhanced comprehension of the intricate relationships under discussion. Significantly, the findings reveal that Work-Family Culture plays a crucial predictive role in influencing perceptions of Organizational Justice among both faculty and administrative staff. More importantly, the study uncovers that Work-Family Culture indirectly affects Job Satisfaction through its impact on Organizational Justice. Discussion This insight underscores the importance of harmonious work-family interactions as a determinant of job-related attitudes and satisfaction levels.